A descriptive study of the reality of the distribution of ambulance centers in urban and rural areas In the Kingdom of Saudi Arabia (The Review of Diabetic Studies, 2025)
This study aims to describe the current reality of the distribution of ambulance centers in urban and rural areas in the Kingdom of Saudi Arabia  highlighting the degree of balance and equity in the geographical allocation of these centers  The study adopts a descriptive research approach that focuses on analyzing existing information and documented data related to ambulance services without introducing experimental or analytical variables  The methodology relies primarily on comparison with previous studies  official reports  and related research in the field of emergency medical services to identify similarities  differences  and emerging patterns in service distribution  The study reviews national and regional literature addressing emergency medical coverage  response times  population density  and geographic challenges affecting ambulance center placement  Particular attention is given to the contrast between urban areas  which often benefit from higher population density and better infrastructure  and rural areas  which may face limitations related to distance  terrain  and resource availability  By comparing findings from earlier research  the study seeks to describe the extent to which current distribution practices meet community needs and support timely emergency response  The results of this descriptive review are expected to provide a clearer understanding of existing strengths and gaps in ambulance center distribution  contributing to informed decision-making and future planning  The study concludes by emphasizing the importance of evidence-based distribution strategies to enhance equity  accessibility  and overall efficiency of ambulance services across both urban and rural regions in the Kingdom of Saudi Arabia .